Cytokine concentration in peripheral blood of patients with childhood obesity - Mai, Jia; Wang, Min; Guo, Ying; Yang, Ling; Xie, HongJian; Mei, Lan; Zhu, ZiYao; Liu, XiaoJuan (Frontiers in Immunology, 2025)
IntroductionObesity is marked by chronic inflammation, with research showing notable changes in cytokines. However, systematic investigations into cytokine level changes are still lacking. This study compared the concentrations of various cytokines in the peripheral blood of healthy controls and obese children.MethodsPeripheral blood samples from test cohort including 5 healthy children and 5 obesity children were used to evaluate concentration levels of 48 inflammatory cytokines by Bio-Plex assay. Diet-induced obese (DIO) mice used to assess whether there were significant differences in the expression of MIP-1b, PDGF-BB. Peripheral blood samples from validation cohort including 44 healthy children and 44 obesity children were used to evaluate concentration levels of MIP-1b, PDGF-BB, IP-10, IL-6, IL-9 and TNF-β.ResultsIn the Bio-Plex assay, there were significant differences in MIP-1b and PDGF-BB levels between healthy and obesity children. Additionally, IP-10, IL-6, IL-9, and TNF-β exhibited a trend of difference between the two groups. However, no significant differences in MIP-1b and PDGF-BB levels were observed between control and DIO mice. Notably, we found that IL-6 exhibited a significant concentration difference between the serum of healthy and obesity children, suggesting the IL-6 may play a key role in the inflammatory response associated with obesity.DiscussionIn summary, our study emphasizes the importance of IL-6 and other cytokines in childhood obesity research and suggests that future investigations should further explore the specific roles of these cytokines in the pathophysiological states associated with obesity, aiming to provide new strategies for the prevention and treatment of obesity.